Preemptive and Reactive Focus-on-Form Instruction: Effect on learning parallel grammatical structures - BOULKROUN, Fouad (Journal of Human Sciences, 2016)
The present study set out to investigate the differential effect of focus-on-form (FonF) instruction. Two research questions were raised: 1) Does FonF instruction,both preemptive and reactive, have a differential effect on learners' interlanguage? 2) Are short-term gains, if at all, maintained in the long-term? Fifty one (51) third-year LMD university English language learners are divided into two groups: a FonF group (N=27), and a Control group (N=24). Parallel structures were selected as the target form. A Grammaticality Judgment Test (GJT) was used to measure accuracy of the target form over the short- and the long-term; therefore, three similar but not identical tests were administered at three temporal times: a pre-test, an immediate post-test, and a delayed post-test. The results of the present study showed that FonF instruction had a differential effect in language learning in both the short- and the long-term. Recommendations for both research and pedagogy are discussed.